The prevalence of menstrual cycle symptoms and their association with mental health and sleep in German exercising women and athletes - Kullik, L.; Stork, M.; Kiel, A.; Kellmann, M.; Jakowski, S. (Journal of Science and Medicine in Sport, 2024)
Objectives Menstrual cycle symptoms are very common in female athletes. However, more evidence about the association between menstrual cycle characteristics and symptoms with sleep and mental health in athletes needs to be gathered. This study aimed to examine this association in German female athletes.